Promoting HOTS via ICT in ESL Classrooms - Liew, Wai Kit; Ganapathy, Malini (2017)
The introduction of the Malaysia Higher Education Blueprint (2015-2025) reinforced the Ministry’s central aspiration to redesign a higher education system which rivals the world’s leading education systems and which empowers Malaysia to compete in the global economy by specifically promoting Information and Communication Technologies (ICT) and innovations that address students’ needs and allows greater personalisation of the learning experience (Ganapathy et al. 2016). “Teachers lack pedagogical knowledge in having the expertise to innovate their practices by integrating higher order thinking skills (HOTS) in their lessons which does not concur with the HOT questions posed in their examinations and assessments”, (Ganapathy & Kaur, 2014). ESL teachers are facing challenges in teaching HOTS as they prefer the simpler old school teaching method and they are only exposed to HOT pedagogies at a surface level. This paper highlights the impact of ICT on promoting HOTS among secondary school teachers in ESL classrooms. It is vital to acquire deeper insights into the current pedagogical practices used by ESL teachers, the types of ICT that they use in their classes, their views on the integration of these skills into the curriculum and the application methods of teaching and learning using ICT to promote Higher Order Thinking Skills (HOTS). In short, ICT has shaped the education setting and it does have the potential to promote HOTS in ESL classroom settings.